2015
DOI: 10.1111/aen.12179
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of diapause in neotropical parasitoids attacking Anastrepha fraterculus (Diptera: Tephritidae) in a subtropical rainforest from Argentina

Abstract: Incidence of diapause in neotropical parasitoid species associated with the tephritid fruit fly Anastrepha fraterculus (Wiedemann) infesting three major host plants collected from the southernmost end of Argentinean Yungas rainforest was studied. Three other objectives were the frequency of diapause according to the fruiting season of Prunus persica (L.) Batsch (peach), Psidium guajava L. (guava) and Juglans australis Grisebach (walnut); the length of diapause period for each recovered parasitoid species; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Under our laboratory-controlled conditions and using mass-reared A. ludens as hosts, we found that diapause in D. areolatus has been maintained after 23 generations, suggesting a genetic component. The developmental time of diapausing individuals ranged from 70 to 281 days, which is shorter than those reported for this species when they were collected in the field in Mexico, Brazil and Argentina (Aluja et al 1998;Carvalho 2005;Ovruski et al 2016). These reports included wild individuals coming from different fruit fly species hosts (A. obliqua, A. ludens, A. fraterculus, A. serpentina Another factor affecting diapause duration is the metabolic reserves of individuals (Ishihara and Shimada 1995;Hahn and Denlinger 2007), because only those larvae with enough nutritional resources will survive this period (Ellers and van Alphen 2002).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Under our laboratory-controlled conditions and using mass-reared A. ludens as hosts, we found that diapause in D. areolatus has been maintained after 23 generations, suggesting a genetic component. The developmental time of diapausing individuals ranged from 70 to 281 days, which is shorter than those reported for this species when they were collected in the field in Mexico, Brazil and Argentina (Aluja et al 1998;Carvalho 2005;Ovruski et al 2016). These reports included wild individuals coming from different fruit fly species hosts (A. obliqua, A. ludens, A. fraterculus, A. serpentina Another factor affecting diapause duration is the metabolic reserves of individuals (Ishihara and Shimada 1995;Hahn and Denlinger 2007), because only those larvae with enough nutritional resources will survive this period (Ellers and van Alphen 2002).…”
Section: Discussionmentioning
confidence: 63%
“…Despite we found that diapausing individuals had a lower pupal weight, -which could mean lower fat reserves -and adults emerging from diapause were smaller, there were no difference in adult percent emergence between the two cohorts. Aluja et al (1998) and Ovruski et al (2016) previously noted the smaller larval and pupal weight of diapausing individuals, but no comparisons had been made on adult dimensions. Wings also were longer in non-diapausing wasps and this could be associated with the greater flight ability observed in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations